ANALISIS E-GOVERNMENT DALAM PENINGKATAN PELAYANAN PUBLIK PADA DINAS KOMUNIKASI DAN INFORMATIKA PROVINSI SULAWESI TENGAH - Risnandar, Risnandar (Katalogis, 2014)
Theobjective of this research was to find out the implementation of e-Goverment in increasingpublic service at comunication and information official of central Sulawesi province. The Main theory employed was e-goverment theory covers (1) content development , (2) competency building, (3) Connectivity, (4) Cyber Laws, (5) citizen Interfaces, and (6) Capital. It was also supported by President Instruction No. 3 year 2003. The research method employed was qualitative research setting. The research setting  was at communication and information official of central Sulawesi province with 5 informants who chosen purposively as the sample. The tehnique of data collection were interview, observation and documentation. The technique of data analysis was descriptive model by Robson With case study approach. The research results showed that the implementation of e-government in Increasing Public Service at Comunication and Information Official of Central Sulawesi  Province  have  run  well  enough  such  as  Capital  and  Content  Development  and Connectivity even tough still need improvement. Competency Building and Citizen interfaces were less cinsidered where as Cyber Laws was not judged because it was nationally so it needed to be improved by Central Government. Primarily, there was two issues encountered in conducting the main  duty  and  function  of  e-Government  section.  The  first  was  infrastructure  availability, supporting facility such as server, computer, and website from Communication and Information Official were lack. The second was human resources availability particulary those had IT background and technical officers to solve administration and digital information issues. To solve the  issues,  e-Government  had  already  done  some  efforts  at  Communication  and  Information Official of Central of Sulawesi Province. The first efforts was providing and requesting infrastructure availability,  supporting  facility of e-Government.  The second  was  asking  to  the secretariat which would be forwarded by Regional Officery Board to provide technical and IT officers to proceed electronic information and administration.